2015
DOI: 10.1590/s1413-41522015020000083662
|View full text |Cite
|
Sign up to set email alerts
|

Desinfecção de efluente anaeróbio com o uso de ozônio/cloro

Abstract: RESUMOO principal objetivo desta pesquisa foi estudar o processo de oxidação, a eficiência da inativação de coliformes e a formação de subprodutos da ozonização, associado com a desinfecção de efluente sanitário anaeróbio proveniente de um reator UASB. Tal evento foi realizado por meio da aplicação das dosagens de ozônio de 5,0 mg.O 3 .L -1 + 10 mg.Cl 2 .L -1 (ensaio 1); ABSTRACTThe main purpose of this research was to study the oxidation process, the coliform inactivation effectiveness, and the formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The increased contact time may have interfered with the reaction time and increased the formation of by-products. El-Rehaili (1995) and Silva and Daniel (2015) also observed this behavior of COD increase when they applied chlorine and ozone/chlorine in sanitary effluents. The authors explain that this behavior is a possible change in the organic matrix by action of the chlorine, making it more accessible to oxidation in tests of COD.…”
Section: Resultsmentioning
confidence: 64%
“…The increased contact time may have interfered with the reaction time and increased the formation of by-products. El-Rehaili (1995) and Silva and Daniel (2015) also observed this behavior of COD increase when they applied chlorine and ozone/chlorine in sanitary effluents. The authors explain that this behavior is a possible change in the organic matrix by action of the chlorine, making it more accessible to oxidation in tests of COD.…”
Section: Resultsmentioning
confidence: 64%
“…Bhatta et al (2015) observed a slight increase in pH values in their study on the treatment of wastewater by ozone produced in dielectric barrier discharge, in agreement with the results found here. Likewise, Silva and Daniel (2015) observed an increase in pH values (p = 0.05) for the ozonized effluents compared to the UASB reactor effluent.…”
Section: Potential Hydrogen (Ph)mentioning
confidence: 75%
“…Bila et al (2004) have shown that the sequence of coagulation-flocculation treatments + ozonation + biological treatment increases the efficiency of the biological treatment stage. Silva and Daniel (2015), by using ozone followed by chlorine disinfection, obtained good removals of biochemical oxygen demand.…”
Section: Ozone Consumptionmentioning
confidence: 99%